InterGenerate : transforming churches through intergenerational ministry - Allen, Holly Catterton (Abilene Christian University Press, 2018)
Leaders in Christian communities are all asking the same question: How can we bring the generations back together? InterGenerate addresses important questions of why we should bring the generations back together, but even more significantly, how we can bring generations back together. In this edited collection, ministers, church leaders, and Christian educators will find valuable, new generational theory perspectives, fresh biblical and theological insights, and practical outcomes backed by current research. InterGenerate offers important guidance on topics including intergenerational spiritual disciplines, transitioning from multigenerational to intergenerational, new research that focuses directly on intergenerational ministry and offers practical outcomes to implement, and benefits of intergenerational ministry for the most marginalized generations. An exciting and distinctive aspect of InterGenerate is the vast diversity of voices--men and women ranging in age from millennials to baby boomers, representing multiple countries and over a dozen denominations--all seeking ways to become more intentionally intergenerational in their outlook and practice. --